Anomii͡a - Kozlov, Vladimir, 1972-; Kozlov, Vladimir, 1972- (Platzkart Productions, 2016)
'Anomie' is centered on three young people in their late teens/early twenties who live in a big Russian provincial city - Olya, Anya and Igor. Although they come from seemingly normal families, they receive no - or confusing - moral guidance from their families and society at large. As a result, they aimlessly drift through life, following just their instincts. One day, what seems to be a minor conflict leads to tragedy... --